Effect of prenatal calcium supplementation on bone during pregnancy and 1 y postpartum. Issue 1 (16th January 2019) - Cullers, Andrea; King, Janet C; Van Loan, Marta; Gildengorin, Ginny; Fung, Ellen B
ABSTRACT: Background: Low calcium intake during pregnancy may cause maternal skeletal calcium mobilization to meet fetal needs. The Recommended Dietary Allowance (RDA) for calcium in nonpregnant, pregnant, or lactating women aged 19–50 y is 1000 mg/d; most women in the United States report consuming 60–80% of the calcium RDA. An insufficient calcium intake could increase maternal bone loss during pregnancy and reduce bone recovery postpartum. Objectives: The aim of this study was to determine the effect of maternal calcium supplementation on peripheral cortical and trabecular bone loss during pregnancy and bone gain postpartum. Methods: A total of 64 women were enrolled in the study at 16 wk of gestation and randomly assigned to receive 1000 mg Ca/d or placebo for the remainder of the pregnancy. Measurements were performed at 16, 26, and 36 wk of pregnancy and at 4 and 12 mo postpartum for serum 25-hydroxyvitamin D and markers of bone turnover. Trabecular and cortical bone mineral density (BMD) and content were assessed at the tibia and radius by peripheral quantitative computed tomography. Results: Mean ± SD daily calcium intake at baseline was 733 ± 350 mg; only 25% of the women met the RDA. Thirty women (47% of those enrolled) remained in the study at 12 mo postpartum. After controlling for baseline bone value, serum 25-hydroxyvitamin D concentrations, length of breastfeeding, and body mass index, the calcium group had significantly greater increases in radial total BMD ( P = 0.02) and tibial cortical BMD ( P = 0.03) at 12 mo postpartum than the placebo group. Trabecular and total BMD at the tibia trended toward higher values ( P < 0.06) in the calcium group than in the placebo group in the same models. Conclusions: These data show that supplemental calcium provided during pregnancy may improve bone recovery postpartum in women consuming a typical US diet. A larger study is warranted to solidify the conclusions. This trial was registered at clinicaltrials.gov as NCT01145573.